Liraglutide reduces lipogenetic signals in visceral adipose of db/db mice with AMPK activation and Akt suppression - Shao Y; Yuan G; Zhang J; Guo X (Dove Medical Press, 2015)
Yimin Shao, Geheng Yuan, Junqing Zhang, Xiaohui Guo Department of Endocrinology, Peking University First Hospital, Beijing, People’s Republic of China Abstract: Liraglutide, a glucagon-like peptide-1 analog, has been proved to reduce body weight and visceral adipose tissue (VAT) in human studies. In this study, we aimed at examining lipogenetic signal changes in VAT after weight-loss with liraglutide in db/db mice. The mice were divided into two groups: liraglutide-treated group (n=14, 8-week-old, fasting glucose. >10 mmol/L, liraglutide 300 µg/kg twice a day for 4 weeks) and control group (n=14, saline). We found body weight gain and food intake were reduced after liraglutide treatment (P<0.05). Compared to the control group, the VAT weights were significantly lower in the treated group (2.32±0.37 g versus 3.20±0.30 g, P<0.01) than that in control group. In VAT, compared with control group, the lipogenetic transcription factors PPARγ and C/EBPα expressions were both reduced with pAMPK and pACC increased 3.5-fold and 2.31-fold respectively, while pAkt and pP38MAPK were reduced 0.38-fold and 0.62-fold respectively (P<0.01). In conclusion, VAT was reduced after weight loss with AMPK activation and Akt suppression with liraglutide treatment, which was associated with reduction of lipogenetic process in VAT. Keywords: liraglutide, visceral adipose tissue, AMP-activated protein kinase, lipogenesis